Justice et répression de la criminalité en temps de peste - Fleur Beauvieux (Criminocorpus)
In contemporary discourse, times of plague are seen as conductive to disorders of all kinds, including rising criminality. The 36 trials dating from Marseilles’ plague of 1720-1722 deliver another image. The repression was particularly directed against moral crimes (rape, prostitution) and theft from trustworthy persons. What was in reality feared the legal personal was the spread of contagion and a lack of respect for authority. The issue of value added to crime in the epidemic context can therefore be posed.